2013
DOI: 10.1161/strokeaha.113.001188
|View full text |Cite
|
Sign up to set email alerts
|

Protamine Does Not Increase Risk of Stroke in Patients With Elective Carotid Stenting

Abstract: Background and Purpose-Reversal of anticoagulation with protamine might predispose to a higher risk of stroke in patients with carotid stenting. We evaluated a national, multihospital patient database to examine the risk of stroke in patients with carotid stenting receiving protamine compared with those who did not. Methods-The Premier Perspective database was used to identify patients who were electively hospitalized for carotid stenting from 2006 through 2011. The incidence of in-hospital mortality and morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The use of protamine has been shown to be safe in carotid revascularization and its routine use is in fact recommended during TCAR. 18,19 If protamine is utilized during TCAR, the overall rates of hematoma (1.0 to 1.5%) formation remains low regardless of the type of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of protamine has been shown to be safe in carotid revascularization and its routine use is in fact recommended during TCAR. 18,19 If protamine is utilized during TCAR, the overall rates of hematoma (1.0 to 1.5%) formation remains low regardless of the type of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its use, clinical thrombosis is relatively rare having been described after deployment of drug eluting stents 37 . Notwithstanding, protamine has been described to significantly diminish the risk of bleeding complications without increasing the risk of clinical thrombosis in carotid artery procedures 38, 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We updated evidence from 2 systematic reviews that addressed this question, 198,199 identifying 3 RCTs [200][201][202] and 13 observational studies that measured relevant outcomes for patients receiving protamine for LMWH/UFH reversal when undergoing invasive procedures, not for major bleeding during VTE treatment. [203][204][205][206][207][208][209][210][211][212][213][214][215] Most studies did not specify whether "heparin" included UFH or LMWH; therefore, we could not analyze according to heparin subgroup. Given that only 74 patients receiving protamine were included in the RCTs, the panel elected to consider only the evidence from the observational studies.…”
Section: Recommendation 20mentioning
confidence: 99%
“…Six studies reported the effect of protamine administration on mortality, 205,206,209,210,212,214 10 studies reported development of major bleeding, 203,[205][206][207][208][209][211][212][213][214] 10 studies assessed the risk of stroke, [203][204][205][206][207][209][210][211]213,214 and 6 studies reported the risk of myocardial infarction. [205][206][207][212][213][214] No studies reported the risk of PE or DVT. The EtD framework is shown online at https://dbep.…”
Section: Recommendation 20mentioning
confidence: 99%